Engendering Islands : Sexuality, Reproduction, and Violence in the Early French Caribbean - Williard, Ashley M. (Book collections on Project MUSE., 2021)
"Engendering Islands demonstrates how problematics of gender played a central role in defining colonial others, male and female, at the moment when slavery was first introduced in the French-controlled Antilles"--